Novel immunotherapy in the treatment of advanced non-small cell lung cancer. Issue 12 (1st December 2016) - Santabarbara, G.; Maione, P.; Rossi, A.; Palazzolo, G.; Gridelli, C.
ABSTRACT: Introduction : Lung cancers remain the principal cause of death cancer-related worldwide with a poor survival rate at five years from diagnosis. In patients with NSCLC harboring specific genetic alterations the anti EGFR TKIs and the ALK TKIs have improved the response rate and the quality of life compared to standard platinum-based chemotherapy. New approaches possibly applicable at the major of patients are needed. Areas covered : The discovery that the immune system plays a fundamental role in the fight against cancer. The cancer cells use mechanisms able to avoid the immune control has led to the development of drugs able to overcome this escape route. The best known checkpoint pathways are the CTLA-4 and PD-1/PD-L1; they suppress T-cell activity in different ways: CTLA-4 regulates T-cell activity at an early stage whereas PD-1 regulates later effector T-cell activity within tissue and tumors. The best characterized checkpoint inhibitors in advanced NSCLC setting are ipilimumab and tremelimumab, (anti-CTLA-4 antibodies), nivolumab and pembrolizumab (anti-PD-1 antibodies), atezolizumab and durvalumab (anti-PD-L1 antibodies). Nivolumab and pembrolizumab have received the FDA and EMA approval for the treatment of NSCLC in second-line setting. Expert commentary : The role played by tumor microenvironment may be the next area of research to overcome the resistance at the checkpoint inhibitors as well as the identification of biomarkers to better select patients. In addition checkpoint inhibitors are investigate in combination with other agent involved in immune control with promising results in solid tumors.